Governance of illegal, unreported, and unregulated (IUU) fishing in Bangladesh: status, challenges, and potentials - Mozumder, Mohammad Mojibul Hoque; Uddin, Mohammad Muslem; Schneider, Petra; Deb, Dibash; Hasan, Mehedi; Saif, Safwa Bente; Nur, As-Ad Ujjaman (Frontiers in Marine Science, 2023)
Illegal, Unreported, and Unregulated (IUU) fishing can result in a loss of revenue, environmental harm, and economic loss for coastal communities, as well as a reduction in fish stocks. The present study is to generate comprehensive knowledge of the historical patterns and current status of IUU fishing in Bangladesh's coastal and marine water. To accomplish this, secondary, qualitative, and quantitative data were gathered utilizing SWOT as the conceptual framework. Cluster analysis was carried out via NVivo for quantitative processing as well as qualitative analysis of data. This study identified that due to the lack of appropriate and robust governmental laws, regulations, and manpower, IUU fishing in Bangladesh is leading extinction of important fish species, biodiversity loss, and rising poverty among fishers. Some potential solutions include raising the standard of living for underprivileged fishermen, improving management and oversight of both artisanal and industrial fishing, motivating and training stakeholders, and coordinating across all levels of stakeholders. This study will serve as crucial guidelines for managing fisheries sustainably and developing legislation, rules, and regulations to prevent IUU fishing in Bangladesh.